TYPHOID IN ISFAHAN AREA - M. Maleki; C. Bolourian; A. Vokhshouri; M. Sajadieh (Tehran University of Medical Sciences, 1975)
245 patients with typhoid fever were admitted in university of Isfahan Medical Centers during the last 4 years are reported here in this study. The diagnosis was confirmed in each case by the history of the exposure physical examination, Widal seroreaction and blood culture test. The highest incidence of the disease occurred between 10-19 years of age, and mostly in summer months, during June, July, when the fresh fruits and vegetables are plentiful for consumption. There were 53 positive blood cultures for salmonella from 245 samples that were cultures. All patients were positive widal seroreaction with raising titer during the course of their illness. The complication were respectively as follow: hemorrhagic disorders 14% from which G.I. bleeding was the commonest form perforation 5% and myocarditis about 3% and other complications. These were arthritis, thromophelebitis and cholecystitis two cases of each are described here. It is worth of mentioning here the occurrence of hepatitis, osteomyelitis the two unusual complications of the disease in this communication.